2006
DOI: 10.1159/000094739
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Three Spilled Gall Stones: One Liver Mass and Two Abscesses

Abstract: Spilled gall stone has been one of the most common complications of laparoscopic cholecystectomy. Spillage occurs in up to 40% of cases; complications related to spillage are rare and can present within weeks to years. We report 3 cases referred to a tertiary centre for management of such complications. The first patient presented with clinical and radiological findings of cyst 1 week after laparoscopic cholecystectomy. She was initially thought to have a hydatid cyst. At laparotomy it turned out to be a liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In laparoscopic procedures, these techniques are more difficult or unavailable and so stones can disappear from view and can become "lost". Studies show that the incidence of spilled gallstones during laparoscopic cholecystectomy accounts for 6 to 40% of procedures performed, while 13 to 32% of such operations result in lost stones [1,2]. Complications from stones that are left within the peritoneal cavity can cause unusual but significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In laparoscopic procedures, these techniques are more difficult or unavailable and so stones can disappear from view and can become "lost". Studies show that the incidence of spilled gallstones during laparoscopic cholecystectomy accounts for 6 to 40% of procedures performed, while 13 to 32% of such operations result in lost stones [1,2]. Complications from stones that are left within the peritoneal cavity can cause unusual but significant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, complications arising from lost stones are rare, occurring in only 1.4% of cases. 2 Spilled biliary stones commonly remain local in the subhepatic region of the peritoneal cavity, but can also migrate to other sites.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of complications arising from these ectopic stones varies based on their location. 1 Many manifest as intraperitoneal or abdominal wall abscesses, but bowel obstruction, cutaneous sinus tracts, urinary bladder fistula, and even an unusual case of cholelithoptysis have been reported. 3 An assessment of the knowledge and practices of general surgeons and residents regarding spilled biliary stones by Khan et al 4 concluded that there was a common lack of awareness about their diverse possible complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, traction sutures on gallbladder may end up in tearing of the organ leading to stone spillage and associated consequences like abscess, fistula formation and other septic complications later on. [4][5][6][7] This possibility further increases in patients with high stone burden. So, we aim at gentle handling of gallbladder and take preventive steps to avoid intraoperative spillage and hence do not use sutures for traction.…”
Section: Discussionmentioning
confidence: 99%